The human, the orchid, and the octopus [compact disc, unabridged] : exploring and conserving our natural world - Cousteau, Jacques, 1910-1997 (Tantor Media, 2008)
Cousteau describes his philosophy about protecting our world for future generations. Weaving stories of his adventures throughout, he and collaborator Susan Schiefelbein address the risks we take with human health, the overfishing and sacking of the world's oceans, the hazards of nuclear proliferation, and the environmental responsibility of scientists, politicians, and people of faith. Cousteau's lyrical, passionate call for action is even more relevant today than when this book was completed in 1996.